BUILDING MANAGEMENT INFORMATION SYSTEM NATIONAL FINAL EXAM QUESTIONS tryout - Marzuki Marzuki Marzuki (STMIK Jakarta, 2003)
In order to improve the quality of a high school graduate / vocational school, various effortshave been made by the respective - respective schools in order to improve the quality of thesegraduates. This effort is intended to improve the quality of education. Which in turn canimprove the academic quality of universities, whereby universities receive only qualifiedapplicants. Evaluation of the monitoring process is carried out continuously and continuousin the end will be able to fix the quality of education. One effort is developing a managementinformation system design problem tryout. With the availability of information about thetryout system was expected that users can perform a variety of analysis and also can providea more accurate exam. Development of information system design is intended as a first stepin increasing the academic quality of universities.